Effects of caffeine on repeated sprint ability, reactive agility time, sleep and next day performance - Pontifex, K. J.; Wallman, K. E.; Dawson, B. T.; Goodman, C. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: This study assessed the effects of caffeine on repeated sprint ability (RSA), reactive agility time (RAT), sleep and next day exercise performance. METHODS: Ten moderately trained male athletes (single-blind, randomized, crossover design) ingested either caffeine (6 mg.kg-1 bm) or placebo 1 h before exercise. Trials were performed on the same day one week apart. Performance measures included a RAT test (10 trials¥10.2 m, separated by 30 s), followed by 7 min of active recovery and then a RSA test (five sets of 6¥20 m sprints with 25 or 60 s of recovery). The RSA was then followed by 5 min of active recovery and another RAT. That night, participants wore a wrist sleep actigraph to bed. Next day, participants repeated the RAT and the first set of the RSA tests. RESULTS: Significant improvements were demonstrated after caffeine ingestion compared to placebo for the combined total time of each set (TT; combined sets 1, 3, 5; 58.947±1.88 vs. 59.683±2.54 s, respectively; P=0.05), best sprint time (BT; next day performance; 3.176±0.10 vs. 3.230±0.12 s, respectively, P=0.01), and % decrement (combined sets 2, 4; 2.866±1.24 vs. 3.801±1.69 s, respectively; P=0.02). Moderate to strong effect sizes were found for % decrement for set 2 (Cohen`s d=-0.82; 1.312±0.65 vs. 2.110±1.20 s for caffeine and placebo conditions, respectively) and for sets 2 and 4 combined (Cohen`s d=-0.63; 2.866±1.24 vs. 3.801±1.69 for caffeine and placebo conditions, respectively). No significant differences were found for RAT or for sleep measures (P>0.05). CONCLUSION: Caffeine improved RSA, including next day performance, but had little effect on RAT or sleep parameters.